A Picture Paints a Thousand Lies? The Effects and Mechanisms of Multimodal Disinformation and Rebuttals Disseminated via Social Media. (3rd March 2020) - Hameleers, Michael; Powell, Thomas E.; Van Der Meer, Toni G.L.A.; Bos, Lieke
Abstract : Today's fragmented and digital media environment may create a fertile breeding ground for the uncontrolled spread of disinformation. Although previous research has investigated the effects of misinformation and corrective efforts, we know too little about the role of visuals in disinformation and fact checking. Against this backdrop, we conducted an online experiment with a diverse sample of U.S. citizens ( N = 1, 404) to investigate the credibility of textual versus multimodal (text-plus-visual) disinformation, and the effects of textual and multimodal fact checkers in refuting disinformation on school shootings and refugees. Our findings indicate that, irrespective of the source, multimodal disinformation is considered slightly more credible than textual disinformation. Fact checkers can help to overcome the potential harmful consequences of disinformation. We also found that fact checkers can overcome partisan and attitudinal filters – which points to the relevance of fact checking as a journalistic discipline.